Elephantopus-type sesquiterpene lactones from a second Vernonanthura species, Vernonanthura lipeoensis - Pollora, Genaro Cesar (2004)
Three new and eight known sesquiterpene lactones were isolated from the chloroform extract of the aerial parts of Vernonanthura lipeoensis. The lactone chemistry of V. lipeoensis resembles that of its fellow Argentine endemic V. nebularum from the same geographical area. The chemistry of these two species is similar to the sesquiterpene lactones chemistry of Elephantopus mollis.